Morphology of açaí palm (Euterpe spp) interspecific hybrids from the Active Germplasm Bank of Embrapa Eastern Amazon (Research, Society and Development, 2024)
The aim of this word was to evaluate açaí palm accessions that are interspecific hybrids between E. oleracea Mart and E. precatoria Mart, with a view to obtaining information on their complementarity and/or superiority in relation to their parents, to subsidize the genetic improvement program. Were evaluated 48 plants from two hybrid accessions for 31 morphological traits: six of which were plant traits, seven inflorescence traits, seven bunch traits and eleven fruit. Preliminary analyses were obtained by testing means and their performances were compared with the H1 and H2 hybrids. For the plant characters, maternal predominance was evident, with a multi-stem type stem, but with a reduction in the number of stipes per plant, long internodes and a greater number of leaves. As for the inflorescence, cluster and fruit characters, this also showed maternal dominance, but with a reduction in the yield of fruit per cluster and the weight of one hundred fruits, the latter being paternally expressed. They also had lower fruit and seed weight, as well as a violet color in the edible part, suggesting a higher anthocyanin content, like the male parent. Some plants from these accessions showed that all three-ovary locules had fertilized. It can be considered that the interspecific hybrid accessions of Euterp palm have a predominance of the maternal character. This information will be useful for supporting new actions in the genetic improvement of the Euterp palm.